2020
DOI: 10.1177/2325967120963054
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Arthroscopic Surgical Treatment of Osteochondral Lesions of the Elbow in Pediatric and Adolescent Athletes

Abstract: Background: Osteochondral injuries of the elbow are limiting and affect the ability of pediatric and adolescent athletes to participate in sports. Purpose: To report short- and midterm outcomes on athletes undergoing microfracture or fragment fixation of osteochondral elbow lesions and evaluate the effects thereof on sporting activity. Study Design: Case series; Level of evidence, 4. Methods: This was a retrospective study analyzing patients who underwent surgical treatment via microfracture or fragment fixati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Both patients returned to playing baseball at 5 months; however, 1 patient stopped pitching. 19 This procedure performed arthroscopically is technically demanding and is best left in the hands of a skilled elbow arthroscopist. However, any competent orthopaedic surgeon should be capable of performing our technique through a small, 2-inch incision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both patients returned to playing baseball at 5 months; however, 1 patient stopped pitching. 19 This procedure performed arthroscopically is technically demanding and is best left in the hands of a skilled elbow arthroscopist. However, any competent orthopaedic surgeon should be capable of performing our technique through a small, 2-inch incision.…”
Section: Discussionmentioning
confidence: 99%
“…Allahabadi and colleagues in 2020 reported excellent postoperative ROM of 2 patients treated with arthroscopic microfracture and BioCartilage implantation. Both patients returned to playing baseball at 5 months; however, 1 patient stopped pitching 19. This procedure performed arthroscopically is technically demanding and is best left in the hands of a skilled elbow arthroscopist.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluating arthroscopic debridement for capitellar OCD have shown favorable outcomes, which further suggest its potential as a first-line operative strategy. Allahabadi et al 29 evaluated outcomes following arthroscopy with microfracture in 26 adolescent athletes and found radiographic healing in all operative elbows. Only 6 athletes modified or discontinued their preoperative level of activity.…”
Section: Treatmentmentioning
confidence: 99%
“…9). 24,25 Alternatively, treatment can include fixation of an unstable osteochondral fragment to the underlying bone using wire or a self-tapping screw. Newer treatments include cartilage repair.…”
Section: Joint-related Procedures Osteochondral Lesionsmentioning
confidence: 99%